PWE-003 Acetarsol is an effective option in the management of refractory proctitis. (8th June 2018) - Argyriou, Konstantinos; Ingram, Richard; Blatt, Rachel; Wilson, Patrick; Samuel, Sunil; Hawkey, Christopher; Moran, Gordon
Abstract : Introduction: There is an urgent need for superior topical therapy for mesalazine-refractory ulcerativeproctitis. Two small preliminary cohort studies have suggested good clinical efficacy data for organic arsenic derivatives such as acetarsol in refractory ulcerative proctitis. Our aim was to describe the effectiveness and tolerability of acetarsol suppositories in a cohort of inflammatory bowel disease (IBD) patients. Methods: We performed a retrospective cohort study by prospectively reviewing maintained clinical records for all patients exposed to acetarsol at the IBD clinic in Nottingham University Hospitals from 2004 to 2017. Response was determined as clinical improvement or improvement in endoscopic appearance. Serum arsenic and C-reactive protein levels were reviewed when available. Non parametric statistical analysis was performed. Data are presented as median and interquartile range Results: 35 patients were prescribed acetarsol suppositories (28 with proctitis, 5 with left-sided colitis, 1 with diversion colitis and 1 with chronic pouchitis). Twenty were males with median age of 44 (34) years and disease duration of 7 (19) years. Nearly all patients had failed mesalazine or corticosteroid-based topical therapy with 20 (57.1%) being refractory to immunotherapy and 3 (8.6%) to anti-TNF therapy. Acetarsol 250 mg bd for at least 4 weeks was prescribed in 75% of the cases. Median treatment duration was 56 days (28). Sixteen patients were exposed to acetarsol more than once. 76.7% of patients achieved clinical response. 3/35 patients had an endoscopic assessment with two of three patients showing endoscopic improvement. 33.3% patients required treatment escalation following acetarsol exposure with two undergoing subtotal colectomy. Five patients (14.3%) stopped acetarsol due to side effects. One patient experienced vomiting, palpitations and sweating, and the other four experienced headache, vomiting, anal itching and paresthesia. Median serum arsenic level was 728.25 (872) nmol/l (<130 nmol/L). Serum arsenic levels were not correlated with patient clinical response nor the need for treatment escalation. Conclusions: Acetarsol suppositories could be an effective and tolerable option in the management of refractory proctitis. A definitive study is urgently warranted to thoroughly investigate the clinical efficacy and safety of this promising drug.